Діелектрична функція квантовo-розмірної тонкої плівки з модифікованим потенціалом Пешля–Теллера - Gasanov, Kh. A.; Guseinov, J. I.; Abbasov, I. I.; Mamedov, F. I.; Askerov, D. J. (Publishing house "Academperiodika", 2018)
The spatial and time dispersions of the dielectric permittivity of an electron gas in quasi-two-dimensional quantum nanostructures are studied. The screening of the charge-carrier scattering potential in a quantum-confined film with a modified P¨oschel–Teller potential is considered for the first time. Analytical expressions for the dielectric permittivity are obtained.